2022
DOI: 10.2459/jcm.0000000000001359
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of edge-to-edge repair of mitral regurgitation on left heart mechanics and health status

Abstract: AimsExamine the impact of acute changes in left heart strain and volumes with percutaneous edge-to-edge MitraClip repair on improvement in health status assessed using Kansas City Cardiomyopathy Questionnaire-12 (KCCQ-12) score.MethodsChanges in left atrial strain, left ventricular (LV) global longitudinal strain (LVGLS), LV end-systolic volume (LVESV), and end-diastolic volume (LVEDV) were evaluated in 50 patients undergoing MitraClip repair for symptomatic primary mitral regurgitation (PMR) and secondary mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…53 Moreover, Ro et al described reduced LA conduit strain combined with decreased LV volumes in patients undergoing MitraClip, 1 month after the procedure. 54 A small study conducted by Scislo et al in patients undergoing TEER of the MV surprisingly showed no improvement in myocardial strains (LV, LA, RV) but deterioration of LARS in some subgroups. 55 Another study showed LA strain decrease after TEER but included only a small number of patients (25% of whom had SMR).…”
Section: Left Atrial Function and Transcatheter Edge-to-edge Repair O...mentioning
confidence: 96%
See 1 more Smart Citation
“…53 Moreover, Ro et al described reduced LA conduit strain combined with decreased LV volumes in patients undergoing MitraClip, 1 month after the procedure. 54 A small study conducted by Scislo et al in patients undergoing TEER of the MV surprisingly showed no improvement in myocardial strains (LV, LA, RV) but deterioration of LARS in some subgroups. 55 Another study showed LA strain decrease after TEER but included only a small number of patients (25% of whom had SMR).…”
Section: Left Atrial Function and Transcatheter Edge-to-edge Repair O...mentioning
confidence: 96%
“…[ 53 ] Moreover, Ro et al described reduced LA conduit strain combined with decreased LV volumes in patients undergoing MitraClip, 1 month after the procedure. [ 54 ]…”
Section: Left Atrial Function and Transcatheter Edge-to- Edge Repair ...mentioning
confidence: 99%
“…Mitral transcatheter edge-to-edge mitral valve repair (M-TEER) with the MitraClip system (Abbott Vascular, Santa Clara, California, USA) represents an option for selected patients with functional mitral regurgitation (FMR), 1–4 having also been associated in some cases with improved left ventricular (LV) strain and volumes 5 . Intra-procedural evaluation of the hemodynamic effect of M-TEER in this setting is still a matter for debate.…”
Section: To the Editormentioning
confidence: 99%
“…Indices of LV enlargement and function add a strong prognostic value. Recent studies suggest that global longitudinal strain has greater value than LVEF, although the cut-off is not uniform 23 . A TAPSE/PASP (pulmonary artery systolic pressure) ratio less than 0.36 mm/mmHg is strongly associated with an increased risk of mortality after transcatheter aortic valve implantation (TAVI).…”
mentioning
confidence: 99%
“…Recent studies suggest that global longitudinal strain has greater value than LVEF, although the cut-off is not uniform. 23 A TAPSE/PASP (pulmonary artery systolic pressure) ratio less than 0.36 mm/mmHg is strongly associated with an increased risk of mortality after transcatheter aortic valve implantation (TAVI). Providing LV unloading, TAVI is associated with the improvement of both TAPSE, PASP and their ratio.…”
mentioning
confidence: 99%